2019
DOI: 10.1111/apha.13398
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiovascular risk in type 2 diabetes patients by insight into radial pulse wave harmonic index

Abstract: Wang Lin provides an insightful explanation as to why the harmonic components of radial pulse waves may be an important set of signs to reveal the state of the ventricular-arterial system. 1 The important basis of the article comes from the "resonance theory" proposed by Wang et al through a series of elegant animal studies. 2,3 Here, we would like to provide further clinical references to point out the important correlation between the harmonic components of the radial pulse wave and the risk of future cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition, we established a five-step HA computation formula for the peripheral volume pulse, described in Section 2.3.2. Hence, the current study obtained results for type 2 diabetes mellitus [14][15][16][17]. It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, we established a five-step HA computation formula for the peripheral volume pulse, described in Section 2.3.2. Hence, the current study obtained results for type 2 diabetes mellitus [14][15][16][17]. It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17].…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that the fourth harmonic component of the radial pulse wave is important for the risk assessment of macrovascular and microvascular events in patients with type 2 diabetes [14], cardiovascular risk [15], and arterial blood pressure waveforms [16], with different radial pulse wave harmonic indices, silent coronary artery disease, and adverse cardiac events [17]. Therefore, our findings for synchronous peripheral volume pulses are consistent with the findings in [14][15][16][17], in which the radial pulse wave was adopted with different harmonic coefficients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation